Comparison of Cr/C and Cr2O3/Z Catalysts on Hydrocracking of Bio Oil from Pyrolysis of Palm Empty Fruit Bunches - Zainal Fanani; Hasanuddin hasanuddin; Addy Rachmat; Muhammad Said (Molekul, 2021)
Bio-oil derived from palm empty fruit bunch is not suitable for fuel purpose due to high acidity and low heating. Cr2O3/Zeolite and Cr/C catalysts was developed to upgrade bio-oil through hydrocracking. The catalyst prepared via impregnation method followed by oxidation-reduction. Ammonia and pyridine adsorption used to evaluate acidity as well as crystallinity assessment by using XRD. Hydrocracking reaction conducted in hydrogen gas flow rates 0.5-3.0 L/min, the surface area of Cr/C catalyst found out 1,497.07-1,652.58 m2/g, whilst the temperatures 450 to 700 ℃ and the catalyst weights between 0.5 to 2.5 g. Acidity calculated from ammonia and pyridine adsorption shows Cr2O3/Zeolite has higher value compare to pristine Zeolite. XRD pattern shows Cr2O3/Zeolite has high crystallinity as indicated by sharp and pointed diffraction peaks. The optimum condition of hydrocracking confirmed by lower density of liquid product. The variables obtained by a separate experiments shows that H2 gas flow rate best at 2.5 L/min, temperature of hydrocracking 500 ℃ for Cr2O3/Zeolite and 600oC for Cr/C whereas weight of Cr2O3/Zeolite catalyst is 1.5 g. The Cr/C catalyst that gave low density product possess 1,554.48 m2/g surface area. GCMS data shows increase on the number of straight chain compounds within the hydrocracking product.